(untitled) (World Bulletin of Social Sciences, 2023)
The article deals with ethnographies and their interpretation. The lexical-semantic analysis of farming ethnographies of Surkhandarya was briefly described. The works related to the research of ethnographisms were studied. Also, the ethnolexical units that are unique in the speech of the inhabitants of the oasis and are used only by a small number of people in communication were discussed. Farming ethnographies related to were researched by types. Information about ethnographic lexemes was given. Also, in this article, important factors in the process of giving ethnographies related to farming and its analysis were studied. Customs and rituals related to farming were partially covered, and the analysis of ethnographies representing working tools related to farming was briefly described.